The Relationship Between Premature Rupture Of Membranes And Leukocyte Levels In Laboring Mothers At Pku Muhammadiyah Mamajang Hospital - Rahmayanti S; Azizah Nurdin; Jelita Inayah Sari; Syatirah Jalaluddin; Rahim Yunus (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Premature rupture of membranes is one of the important complications in Obstetrics related to birth complications and other complications in the mother and fetus. Objective: to determine the relationship between the incidence of premature rupture of membranes with leukocyte levels in laboring women at PKU Muhammadiyah Mamajang Hospital, Makassar City. Methods: This study was a quantitative study with an observational analytic research design through a cross sectional approach. The population was all laboring mothers and recorded in the register book and medical record records at PKU Muhammadiyah Mamajang Hospital, Makassar City in 2020 and 2021, the sample obtained was 101 respondents. This study used purposive sampling technique data processed using SPSS with chi-square test. Results: the relationship between age, parity, leukocyte levels and the incidence of premature rupture of membranes successively obtained a p-value, namely: p-value 0.003<0.05, p-value 0.041<0.05, p-value 0.004<0.05. And for the relationship between leukocyte levels of pregnant women with the incidence of premature rupture of membranes at term and preterm gestation, the p-value is 0.040 <0.05. Conclusion; There is a relationship between leukocyte levels and the incidence of premature rupture of membranes.